(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The identity of the person is an essential and distinctive element of his individual heritage and constitutes a real right. Two recent decisions, one of the Constitutional Court of May 2020 n. 127 and one of the Supreme Court, of September 2020 n. 19824, provided an opportunity to reflect on the issue of protecting the identity of children. In the first case of the child born from insemination heterologous and, in the second, of the child born of an anonymous mother, because, in both cases, there are significant problems of balancing the right of identity with other relevant rights or interests.